The Influence of Influencer Marketing and Brand Awareness on Purchasing Decisions of Skintific Products among FEB Universitas Labuhanbatu Students - Ahmad Yahdil Fata Rambe; Rossiyana Rossiyana; Mhd. Amin (LPPM Universitas Labuhanbatu, 2026)
This study aims to examine the influence of influencer marketing and brand awareness on the purchasing decisions of Skintific products among students of the Faculty of Economics and Business, Universitas Labuhanbatu. The study used a population of 80 fifth-semester Management students, applying a saturated sampling technique. Data were collected using Likert-scale questionnaires (1–5) and analyzed through validity and reliability tests, as well as multiple linear regression using SPSS. The results indicate that influencer marketing has a positive and significant effect on purchasing decisions, as does brand awareness. Simultaneously, both variables significantly influence purchasing decisions, explaining 73.8% of the variation. These findings confirm that marketing strategies through influencers and the enhancement of brand awareness play a crucial role in shaping the buying intentions of young consumers, particularly students who actively use social media as a source of skincare product information.Keywords : Influencer Marketing; Brand Awareness; Purchasing Decision; Students